Migrações, fronteiras e espaços interculturais - Reis, Hiliana (2008)
The contributions of Cultural Studies in the field of Communication became relevant, due to the constant migration of Latin American and African students to Brazil, in search for qualified university education. The analysis of the use of digital mediations by this group emphasizes issues concerning the interface between Communication, Politics and Education. How the social cultural practices are revealed by and interfere in their choices and uses of digital media? The qualitative methodology applied, based on case studies, made evident that elements concerning the cultural structure of Latin American and Africans students are significant in their lives histories and lead to the use of digital media. The articulation of themes such as nacionality, etnic background, academic education and the appropriation of digital media connect the use of the computer with social exclusion and antidemocratic models related to the contribution of the logics underlying the digital net.